Penerapan Bahan Ajar Berbasis Literasi Untuk Meningkatkan Keterampilan Membaca Peserta Didik Slow Learner Di Sekolah Dasar - Nuri Annisa; Nofrita (Jurnal Elementaria Edukasia, 2023)
Literacy is a fundamental aspect that an individual must have. A literate society has an important role in the progress of a country, but in reality, literacy in Indonesia is still relatively low compared to other ASEAN countries. This low literacy has an impact on many things, especially education. There are many efforts we can make to minimize the low level of literacy in Indonesia, one of which is by providing quality teaching materials so that students will feel interested in reading and enjoy reading activities. The method used in this research is a quantitative method. This research uses a pre-experimental quantitative research method with the research design, namely one group pretest-posttest design with a research method used to examine a certain population or sample and give an initial test (pretest) and a final test (posttest) on the sample group to see improvements. The aim of this research is to find out how literacy-based teaching materials are implemented and whether literacy-based teaching materials can improve the reading skills of slow learner students. Based on research results, literacy-based teaching materials can improve the reading skills of slow-learner students.